2004
DOI: 10.1081/lft-120038725
|View full text |Cite
|
Sign up to set email alerts
|

Size Exclusion Chromatography: Characterization of Heavy Petroleum Residues. Application to Resid Desulfurization Process

Abstract: Size exclusion chromatography (SEC) is still the only of the existing analytical methods that can easily and routinely provide information on relative asphaltene molecular weight distributions. However, molecular weight characterization still suffers from several physicochemical drawbacks such as association of molecular units, adsorption on column material and lack of appropriate standards, which are not always underlined in the petrochemical literature where SEC is used as a routine analytical tool. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 29 publications
(29 reference statements)
6
53
0
Order By: Relevance
“…For instance, size exclusion chromatography is used to determine the molar masses of asphaltenes, residues and effluents of hydroconversion processes. Merdrignac et al (2004) demonstrated that size exclusion chromatography, although unsuitable for absolute determination of molar masses for these compounds, can be used to compare the molar mass distributions under given analytical conditions. Light, X-ray and neutron scattering techniques (Ravey and Espinat, 1990;Espinat, 1991) have also used in the determination of molar masses.…”
Section: Determination Of Molar Massesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, size exclusion chromatography is used to determine the molar masses of asphaltenes, residues and effluents of hydroconversion processes. Merdrignac et al (2004) demonstrated that size exclusion chromatography, although unsuitable for absolute determination of molar masses for these compounds, can be used to compare the molar mass distributions under given analytical conditions. Light, X-ray and neutron scattering techniques (Ravey and Espinat, 1990;Espinat, 1991) have also used in the determination of molar masses.…”
Section: Determination Of Molar Massesmentioning
confidence: 99%
“…As conversion proceeds therefore, the residues processed become less stable, sometimes precipitating to such a point that they block up the pipes and the exchangers. Studies conducted on asphaltenes to investigate the conversion mechanisms have been described in several publications: Merdrignac et al (2004), Bartholdy and Andersen (2000), Wiehe (1992 and1993). Many questions are still unanswered, however, since prediction of flocculation phenomena remains a challenge: -what is the maximum conversion rate possible for a given crude without destabilising the effluents?…”
Section: Introduction -Reminder Of the Stakesmentioning
confidence: 99%
“…Asphaltene content, asphaltene-to-resins ratio, the metal impurities level and the size of asphaltenes are critical properties for catalyst activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…SEC was performed on a Waters Alliance 2695 system, using a refractive index detector described elsewhere (Merdrignac et al, 2004). The system was controlled using an Empower chromatography manager.…”
Section: Size-exclusion Chromatography (Sec)mentioning
confidence: 99%